2004
DOI: 10.1029/2004gl020914
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic storm ring current injection modeled with the Rice Convection Model and a self‐consistent magnetic field

Abstract: [1] We simulate plasma transport from the plasma sheet to the ring current, for the first time including the feedback effect of the drifting particles on both the electric and magnetic fields. Results suggest that strong, steady adiabatic convection throughout the middle plasma sheet leads to a highly stretched inner plasma sheet, but no ring current particle flux increases. We subsequently impose a substantial reduction of the specific entropy PV 5/3 near midnight outside 10 R E , where P is particle pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
122
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(132 citation statements)
references
References 19 publications
(14 reference statements)
10
122
0
Order By: Relevance
“…Earthward convection penetrates deeper into the inner magnetosphere if the nearEarth X-line (NEXL) forms closer to Earth to produce closed flux tubes with lower values of specific entropy for injection of ring cur rent [Lemon et al, 2004].This is consistent with the ring current injection conjecture proposed by this article's co-author Joe Kan (University of Alaska Fairbanks) that the ring current intensity increases with X-line formed closer to Earth. Unfortunately there was no time for meaningful discussion of the conjecture.…”
Section: Smc Events Without Substormssupporting
confidence: 82%
“…Earthward convection penetrates deeper into the inner magnetosphere if the nearEarth X-line (NEXL) forms closer to Earth to produce closed flux tubes with lower values of specific entropy for injection of ring cur rent [Lemon et al, 2004].This is consistent with the ring current injection conjecture proposed by this article's co-author Joe Kan (University of Alaska Fairbanks) that the ring current intensity increases with X-line formed closer to Earth. Unfortunately there was no time for meaningful discussion of the conjecture.…”
Section: Smc Events Without Substormssupporting
confidence: 82%
“…They can penetrate deep into the inner magnetosphere through interchange instability [e.g., Wolf et al, 2009], which often leads to magnetic field dipolarization and particle energization during storm times [Ohtani et al, 2007;Gkioulidou et al, 2014;Turner et al, 2015]. On the other hand, numerical simulations of Lemon et al [2004] suggested that it was difficult for lossless adiabatic convection to transport a fully populated flux tube from the middle plasma sheet into the ring current region even when the cross polar cap potential (CPCP) drop is 100 kV. This is because the inflation of the magnetic field induces a dusk-to-dawn induction electric field on the nightside that partially counterbalances the convection electric field.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the Rice Convection Model (RCM) and the Rice Convection Model-Equilibrium (RCM-E) have been extensively used to investigate how the plasma inside depleted flux tubes is transported in the nearEarth region [Lemon et al, 2004;Zhang et al, 2008;Zhang et al, 2009aZhang et al, , 2009bYang et al, 2008Yang et al, , 2011Yang et al, , 2012Yang et al, , 2014aYang et al, , 2014b. The model uses the slow-flow approximation and assumes an isotropic pressure distribution along magnetic field lines.…”
Section: Introductionmentioning
confidence: 99%
“…[25] The simulations of Lemon et al [2004] suggested that strong sunward convection is capable of injecting plasma sheet flux tubes with PV 5/3 < $0.08 nPa(R E /nT) 5/3 deep into the inner magnetosphere. Higher entropy flux tubes moved around the flanks without entering the inner magnetosphere.…”
Section: Ring Current Intensity Increases If the X-line Forms Closer mentioning
confidence: 99%